Financial market implications of marketing actions and the disclosure of marketing information - MOON, Sungkyun (Institutional Knowledge at Singapore Management University, 2020)
This dissertation contributes to marketing literature by examining the effects of marketing actions and the disclosure of marketing information through the financial market perspective that has high managerial relevance and policy implications. Specifically, the first essay provides the first empirical examination of the effects of the disclosure of advertising spending on investors’ and analysts’ uncertainty. It is responsive to calls by Marketing Science Institute and Marketing Accountability Standard Board to examine the consequences of disclosure of marketing metrics. The second essay examines the effect of advertising spending on firm value and explores firm and market level contingency effects. By doing so, the second essay identifies relevant firm financial conditions and market environments, and provides managerial implications. Importantly, for the identification of the proposed effects in both essays, I apply the instrumentation strategy to address the potential endogeneity concerns related to disclosure of advertising spending and the level of advertising spending. Specifically, I develop and propose instruments alternative to those frequently used in extant literature in marketing. Accordingly, this dissertation contributes to marketing literature by proposing alternative instruments that can mitigate the critiques by Rossi (2014) and Angrist (2014) and potentially be used in other contexts.